THE EFFECTIVENESS OF THE LEARNING CYCLE 5E INTEGRATED WITH PROBLEM BASED LEARNING IN ENHANCING STUDENTS’LEARNING MOTIVATION IN ISLAMIC RELIGIOUS EDUCATION AND CHARACTER EDUCATION - Hilda Aulia Zahra; Beti Susilawati; Syamsuri Ali (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2026)
This study was conducted to analyze the effectiveness of the Learning Cycle 5E model. integrated with Problem Based Learning (PBL) in enhancing students’ learning motivation in the context of Islamic Religious Education (PAI) and Character Education Conducted at SMP Negeri 37 Bandar Lampung. this research adopted a quantitative approach with a quasi experimental posttest-only control group design.involving an experimental class and a control class. The data were obtained through a learning motivation questionnaire that had undergone validity and reliability testing, and subsequently analyzed using an an independent samples t-test was employed to examine differences in learning motivation levels between the groups. The results demonstrate that the application of the Learning Cycle 5E model based on PBL significantly enhanced students’ learning motivation compared to conventional instruction. Improvements were reflected in students’ active engagement, intrinsic motivation, self confidence, and the strengthening of religious attitudes throughout the learning process. The originality of this study stems from the integration of the Learning Cycle 5E model with the Problem Based Learning approach within junior secondary PAI and Character Education, an area that has rarely been examined in an integrated manner. The study’s implications suggest that this model fosters interactive, meaningful, and student centered learning, thereby serving as an innovative alternative strategy to enhance learning motivation while simultaneously reinforcing students’ character development. Theoretically, this research contributes to the advancement of constructivist learning studies in religious education, while practically providing evidence-based guidance for teachers in designing effective and contextually relevant instructional practices for contemporary learners.